2000
DOI: 10.1016/s0304-3959(00)00340-7
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal brain chemistry in chronic back pain: an in vivo proton magnetic resonance spectroscopy study

Abstract: The neurobiology of chronic pain, including chronic back pain, is unknown. Structural imaging studies of the spine cannot explain all cases of chronic back pain. Functional brain imaging studies indicate that the brain activation patterns are different between chronic pain patients and normal subjects, and the thalamus, and prefrontal and cingulate cortices are involved in some types of chronic pain. Animal models of chronic pain suggest abnormal spinal cord chemistry. Does chronic pain cause brain chemistry c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
170
1
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(193 citation statements)
references
References 35 publications
16
170
1
4
Order By: Relevance
“…In this study, the location of the probes measured changes in the dorsal and lateral prefrontal cortex (DLPC). Functional and other imaging studies of pain have suggested an important role of this area of the brain in both acute (Svensson et al, 1997;Becerra et al, 1999;Becerra et al, 2001) and chronic pain conditions (Grachev et al, 2000;Apkarian et al, 2004). A number of projections that are received by the prefrontal cortex originate in visual, auditory, parietal and cingulate regions, as well as subcortical regions such as the amygdala (Barbas, 2000) and hypothalamus (RempelClower and Barbas, 1998).…”
Section: Activation In the Frontal Regionmentioning
confidence: 99%
“…In this study, the location of the probes measured changes in the dorsal and lateral prefrontal cortex (DLPC). Functional and other imaging studies of pain have suggested an important role of this area of the brain in both acute (Svensson et al, 1997;Becerra et al, 1999;Becerra et al, 2001) and chronic pain conditions (Grachev et al, 2000;Apkarian et al, 2004). A number of projections that are received by the prefrontal cortex originate in visual, auditory, parietal and cingulate regions, as well as subcortical regions such as the amygdala (Barbas, 2000) and hypothalamus (RempelClower and Barbas, 1998).…”
Section: Activation In the Frontal Regionmentioning
confidence: 99%
“…All spectra were transformed into a standardized scale using the Scion Image analysis package (Scion Corp, Frederick, MD, USA) and analyzed as described earlier. [36][37][38][39] The relative concentrations of NAA (the dominant peak in 1 H-MR spectra, positioning at 2.02 parts per million (ppm)) were meas-ured relative to the peak of creatine/phosphocreatine complex (this creatine/phosphocreatine complex we label as Cr (3.0 ppm; internal standard)). The rationale for using the ratios method relative to Cr has been explained.…”
Section: Molecular Psychiatrymentioning
confidence: 99%
“…In our previous studies of different cognitive states (studies of anxiety, 36,37 pain, 38 anxiety and pain 39 ) using in vivo proton magnetic resonance spectroscopy ( 1 H-MRS), we demonstrated a sensitivity of the method for documentation of chemical-perceptual characteristics of the human personality, which can be captured by monitoring the regional changes of neuronal marker N-acetyl aspartate (NAA) in relation to specific cognitive measures. These studies already demonstrated that this approach could become a new method for tracking the long-term brain chemical characteristics of anxiety and pain, and, possibly some other cognitive states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been exploited in a study of patients with chronic low back pain that showed a decrease in NAA concentration within the dorsolateral prefrontal cortex. It remains to be determined how useful MRS is for assessing efficacy of drug action in pain patients; however, as the changes in metabolite profiles in chronic back pain patients were related to certain subjective measures on the McGill pain questionnaire (21), it might prove yet to be a useful noninvasive measure of drug efficacy.…”
Section: Potential Solutions That Could Improve Drug Developmentmentioning
confidence: 99%